THE EFFECT OF ANTICIPATION GUIDE STRATEGY ON STUDENTS’ READING COMPREHENSION - Mezia Kemala Sari; Lisa Rana Sari (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2019)
This research focuses on the influence of anticipation guide strategy on students' reading comprehension at the twelfth grade of MA KM Muhammadiyah Padang Panjang, 2017/2018 Academic Year. The research design was an experimental research conducted to the Science class as the participants of the research. The instrument of this research was a multiple-choice test distributed as the pre-test and post-test. As the result, the students’ reading comprehension became significantly better after being taught by the anticipation guide strategy. It is found that the pre-test average score was 42.36, and after the treatment, the post-test average score was 75.7. The result shows that the anticipation guide strategy has significant influence on the student’s reading comprehension.